Low cost center pivot irrigation monitoring systems based on IoT and LoRaWAN technologies - Mateos Matilla, D.; Diego Manuel Jiménez Bravo; Murciego, Á.; Valderi Leithardt; Sales Mendes, A. (2020 IEEE International Workshop on Metrology for Agriculture and Forestry, MetroAgriFor 2020 - Proceedings, 2020)
An increase in the irrigation demand has been projected in Europe, especially in the countries with the highest proportion of irrigated agricultural areas, such as Italy and Spain. This has led to advances in the field of irrigation systems, as center pivot systems which have facilitated the labor of farmers because of their automation. However, the monitoring of these systems together with the early detection of problems in their operation has become a key aspect during a farmer campaign. To answer this need, different solutions have been proposed from the ICT area and the Precision Agriculture field. In this work, the main communication and sensor technologies used for monitoring irrigation with pivots are analyzed. Two low-cost systems based on IoT technologies, GPS and LoRaWAN are proposed for the monitoring of this type of irrigation systems. Finally, the results obtained after its installation in two maize crops are presented and the conclusions obtained after the use of both systems are discussed.